A translation framework: from language to communication - Bordyuk, L.; Semotyuk, O. (Українські технології, 2006)
The insight into the conceptual nature of the translation process has been given Cultural differences and discourse strategies as an integral part of the translation process have been regarded.
Keywords: translation framework; cross-cultural communication; a decision-making process; an interdisciplinary character